'Dip Catalysts' Based on Polymer‐Metal Nanocomposite Thin Films: Combining Soft‐Chemical Fabrication with Efficient Application and Monitoring. Issue 12 (11th October 2018) - Madhuri, U. Divya; Saha, Jony; Radhakrishnan, T. P.
Abstract: Nanocatalysts can potentially harmonize the advantages of homogeneous and heterogeneous catalysts, provided they are sequestered in a suitable host matrix that not only enables convenient introduction into repeated reaction cycles, but also allows facile access for the reaction system. Polymer‐metal/semiconductor nanocomposite thin films fabricated through an in situ protocol offer a promising solution involving eco‐friendly synthesis and sustainable application. Salient features of the approach include (i) the simple, soft‐chemical fabrication methodology that also allows real‐time observation of the catalyst formation, (ii) efficient nanocatalyst action through the facile movement of the reactants and products to and from the catalyst site enabled by the swelling of the polymer matrix, and (iii) realization of the 'dip catalyst' concept that emphasizes the ease of insertion and retrieval of the thin film into and from the reaction system, coupled with the feasibility of effective catalyst monitoring through multiple uses. An overview of the nanocomposite thin film fabrication, types of nanostructures that have been reported in this context, deployment of the thin film 'dip catalysts' in several reactions, and emerging new directions in the field and open problems are presented. Abstract : Dapper dipping : Efficient soft‐chemical fabrication, recycling and monitoring are enabled by the 'dip catalyst' design of polymer‐metal nanocomposite thin films. This Focus Review highlights the creation of these catalysts and their sustainable use.